The Role of Management Information in Education Management - Zubek, Michał (Journal of Public Governance, 2021)
Objectives: In management processes, information is very important, but in the educational system its role is crucial. According to the author, decisions made in the current Polish educational system are not based on mechanisms derived from management science which includes the role of information. The aim of this article is to present the role of management information in the educational system, the main mission of which is to overcome the distance between the Polish educational system and modern, worldwide educational standards. Research Design & Methods: The conducted quantitative research was based on critical analysis and interpretation of sources from literature as well as on the observation of specific phenomena, behaviours, and events. As far as qualitative methods are concerned, the author used Time-Driven Activity-Based Costing and an analysis of municipal budgetary accounts, which was treated as a credible and reliable source of information of the studied phenomena. Findings: The results of the TDABC prove that the potential of the Polish educational system has not been fully exploited. Implications / Recommendations: The system’s time and financial reserves could be used to minimise the distance between the Polish education standards and modern educational requirements if the information channels were made more efficient. Contribution / Value Added: The author points to potential further research on the role of management information in the educational system. Article classification: research article JEL classification: M540 Personnel Economics: Labor Management